Incidence of suicide cases during social distancing (Research, Society and Development, 2022)
This study aims to analyze suicidal behavior during social distancing imposed as a measure to combat the COVID-19 pandemic caused by the SARS-COV2 virus. Therefore, scientific articles were used for literary review, medical records and medical exams from the Legal Medical Institute of the municipality of Cascavel-PR were used to collect data so that it was possible to make a comparison between suicide cases during the pre-pandemic period and the post-pandemic period. This study was carried out in a retrospective, cross-sectional and quantitative manner. Fisher's test was used for statistical analysis, with a significance level of p